Pesantren Dan Homoseksualitas Kaum Santri (Studi Pada Pesantren Tua Salafiyyah dan Khalafiyyah di Kota Santri Jawa Timur) - Azam Syukur Rahmatullah; Muhammad Azhar (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2018)
The research has the effort to know a behavior of LGBT in Pesantren. The assumption until now, Pesantren was innocent and be the free zone of LGBT. This research is using qualitative and ethnomethodology’ approach. The location of research is in Pesantren Salafiyyah Kyai Kholil Bangkalan Madura, that old Pesantren Salafiyah in Madura. The other Pesantren is Pesantren Al-Hikam Bangkalan Madura that old Pesantren Khalafiyah in Madura. The results of research are; First, kinds of behavior that indicate LGBT in Pesantren are (1) kakak-adikan, kobel, mojok, kelon. The Second, the efforts from two pesantren are same handling based cognitive, spiritual and physical. The handling in Pesantren Salafiyyah Kyai Kholil Bangkalan, are three enhance; (1) period beginning of kesantrian (2) period of unification santri (3) period the end of kesantrian. The handling in Pondok Pesantren Al-Hikam with several methods; (1) assessment of kitab method (2) punishment method (3) counseling method (4) assessment and enlightenment method (5) supervision without served.